Maternal beliefs about infant-directed speech misalign with interactions with their infants - Ramirez, Alexus G.; Herbst, Elana; Golinkoff, Roberta Michnick (Frontiers in Developmental Psychology, 2023)
Infant-directed speech (IDS) refers to how people in many societies talk with young children. Compared to speech directed to an adult (ADS), IDS includes a slower rate, fewer words per utterance, higher-than-average pitch, and elongated vowels. Although many benefits are associated with using IDS, there is little information on what parents think about IDS. The current study asked: 1) How do mothers conceptualize IDS; 2) Is there an alignment between mothers’ IDS beliefs and their speech register when teaching a new word to their child; and 3) How do mothers’ IDS beliefs associate with children’s expressive language and performance on a word learning task? Fifty-three mothers and their 15- to 21-month-old monolingual English-reared infants (Mage= 17.92, SD = 1.99, 23 males) participated. Mothers were asked to teach their child a novel word and to complete the Parent Language Belief Questionnaire (PLBQ). Mothers’ IDS was recorded as they taught their child a novel word and was compared to their ADS from interacting with the experimenter. Results revealed that mothers had mixed beliefs about their use of IDS. Yet, most mothers used IDS as they taught their child a novel word. Lastly, mothers’ IDS beliefs did not predict children’s language skills or word learning at test. As the positive benefits between IDS and children’s language development have been documented (e.g., Ma et al., 2011), identifying the barriers surrounding why parents may not use IDS with their children is essential.